Consumerism on Clubhouse Exclusivity from Jean Baudrillard’s Perspective - Farisha Sestri Musdalifah (Warta Ikatan Sarjana Komunikasi Indonesia, 2021)
Clubhouse became increasingly popular since the beginning of 2021, especially in Indonesia. After being popularized by public figures who opened live discussions and chats through this audio-based platform, Clubhouse rose in popularity. However, not everyone can become a Clubhouse user, because this platform can only be downloaded by Apple devices and must be invited by users who already have a Clubhouse account. This requirement increases the demand for Clubhouse invitations. Some even sell these invitations online at varying prices. This paper attempts to examine the phenomenon of Clubhouse popularity using Jean Baudrillard's perspective. This descriptive qualitative approach analyzes Clubhouse's popularity using Jean Baudrillard's perspective about consumer society. The results of this study indicate that the consumer society conceived by Baudrillard is still relevant in dissecting the Clubhouse phenomenon. Its exclusivity makes the users use Clubhouse not because of the features offered, but based on the desire to be different from others by affirming their social class. Becoming a Clubhouse user means using Apple products and being part of the upper class by following the latest social media trends. This phenomenon illustrates that capitalism continues to work to create endless needs under the guise of exclusivity to make its consumers feel special and different.